(untitled) (Comparative Professional Pedagogy, 2022)
The article analyzes the problem of assessment competence of future teachers in foreign countries and in Ukraine. The article proves that assessment competence is a structural element of professional competence of future teachers in general and physical education teachers in particular. The purpose of the article is to theoretically analyze the problem of assessment competence of future teachers in foreign countries and in Ukraine. In the result of the analysis of scientific elaborations of foreign and domestic scientists, we can state that the comparison of European and domestic models of assessment competence showed a number of differences. They exist due to socio-economic factors (in Ukraine today we cannot name a large number of educational programs with foreign language teaching, high mobility scientific and pedagogical staff and applicants for higher education in various specialties who participate in exchange programs) and teaching traditions (giving preference to basic education over vocational and economic-oriented). In European educational programs, there are no separate courses on mastering higher education students’ assessment competence, but there are three types of master’s programs in assessment (assessment “in general”; assessment with a focus on statistical and sociological methods; assessment in specific areas of governmental policy); additional education programs (advanced training courses) and assessment courses in undergraduate programs. Regarding the Ukrainian system of bachelor’s degree training for teachers in general and physical education teachers in particular, its research showed that in the absence of separate courses on mastery of assessment knowledge and skills, some programs contain elements of control and assessment activities and concise information blocks of assessment. In the Ukrainian educational system, evaluative information is insufficiently systematized and considered in the context of various educational disciplines.